The Double Sawi-Shehu Transform (European Journal of Pure and Applied Mathematics, 2025)
This research combines the Sawi and Shehu transforms into a unified framework called the Double Sawi-Shehu Transform. We study its core features such as when it exists and how to recover the original function. We also develop improved methods for solving partial differential equations in multiple dimensions and extend the double convolution theorem to two-dimensional problems. Practical examples show how this approach simplifies complex calculations in physics and other sciences proving its effectiveness.
Keywords: The Sawi transform; The Shehu transform; The double integral transform; The double Sawi-Shehu transform